Pengaruh Kurs, Cadangan Devisa, dan Konsumsi terhadap Ekspor Bersih Alat Transportasi Laut Indonesia - Aditya, Bagus; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Indonesia is an archipelagic state which most of its area is water. Therefore, it needs marine transportation to support national economic activity. Though export of marine transportation production is increasing rapidly, Indonesia still importing this commodity. By using Vector Auto Regression (VAR), this study aimed to identify the influence of U.S dollar exchange rate, foreign exchange reserves, number of loading/unloading goods, and number of passenger in port to net export of Indonesian marine transportation production in the period of 1995-2010 simultaneously and partially. It is known that U.S dollar exchange rate, foreign exchange reserves, number of loading/unloading goods, and number of passenger in port, simultaneously and significantly, influence thenet export of Indonesian marine transportation production on the period of 1995-2010. Meanwhile, partial test shown that the net export of Indonesian marine transportation production influenced by net export variables in four previous quarterly; U.S dollar exchange rate of two, four, seven, and eight previous quarterly; foreign exchange reserves of one, two, and four  previous quarterly; and number of loading/unloading goods in the four previous quarterly. Number of passenger in port did not influence the net export partially and significantly.
Keywords: net export; exchange rate; foreign exchange reserves; number of loading/unloading goods; number of passenger; VAR test